The Role of Social Studies Teacher to Growth Social Skills of Student - Nurmarini; Tetep (SAHUR Journal, 2022)
Social studies learning is learning where students are taught to have knowledge and sensitivity to the surrounding community environment. As in the Yakha Banyuresmi Middle School, the role of the teacher here is not only to provide teaching through materials, but outside the classroom. Such as the development of social skills. and behavior related to oneself (intrapersonal), behavior related to others (interpersonal), and behavior related to academics. The problems that arose when researchers conducted research at YAKHA Junior High School Banyuresmi included: the lack of social studies teachers which resulted in teaching and learning that was not conducive, and the ability of teachers was still minimal, with less than 5 years of teaching experience. Teachers still use the lecture method, so students feel bored and sleepy in class. The delivery of social studies material is still monotonous, so it is found that students underestimate the teacher when learning. The reason for choosing Yakha Junior High School is to find out how the ability of social studies teachers to develop social skills in students, and to overcome students' attitudes that are still deviant. The objectives to be achieved include: 1) knowing the role of social studies teachers in developing the social skills of students at SMP Yakha Banyuresmi. 2) knowing the supporting and inhibiting factors in developing the social skills of students at SMP Yakha Banyuresmi. 3) find out the correlation between the role of social studies teachers on the development of students' social skills. In this study using quantitative methods with a population of 101 class VII students and a sample of 31 students. Describe the role of social studies teachers on the social skills of students based on each variable. The results of the study and the results of statistical calculations on the two-tail t-test, the t-count value < t-table value was obtained. So that there is a correlation between the role of social studies teachers on the development of social skills of students at SMP Yakha Banyuresmi. The role of social studies teachers includes teachers as informers, organizers, motivators, directors, initiators, transmitters, facilitators, mediators, and evaluators for the development of students' social skills that are intrapersonal, interpersonal, and academically related.